2022
DOI: 10.19053/01211129.v31.n59.2022.13896
|View full text |Cite
|
Sign up to set email alerts
|

What is There About DevOps Assessment? A Systematic Mapping

Abstract: DevOps has been established as a framework used by software development companies seeking to set mechanisms to automate their development processes. Consequently, over the last decade, many companies have adopted DevOps to support their project’s development process and perform continuous improvement tasks to ensure that it is applied correctly. To achieve this, companies are looking for solutions that allow them to evaluate the degree of implementation of DevOps in their internal processes. In this sense, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…After executing a systematic mapping of the literature (SML), as reported in [35], it was analyzed to identify the solutions proposed by different authors in relation to the definition of processes, models, techniques and/or or tools to evaluate DevOps in software companies. Three types of studies were identified: (i) exploratory studies, (ii) methodological solutions, and (iii) tools.…”
Section: A Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…After executing a systematic mapping of the literature (SML), as reported in [35], it was analyzed to identify the solutions proposed by different authors in relation to the definition of processes, models, techniques and/or or tools to evaluate DevOps in software companies. Three types of studies were identified: (i) exploratory studies, (ii) methodological solutions, and (iii) tools.…”
Section: A Backgroundmentioning
confidence: 99%
“…However, adopting DevOps in software companies is not a simple task [33], to minimize the risk of error in its adoption, they must establish mechanisms that allow quantifying how it is applied in their projects and identify improvement opportunities to fine-tune their practices and improve their internal processes [34]. The efforts and proposals related to the evaluation of DevOps in software companies were identified with a systematic mapping of the literature carried out in [35]. Two mechanisms were used to define methodological solutions (models, metrics, certification standards) and tools developed by active players in the industry that seek to assess DevOps in multiple ways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation